2016
DOI: 10.1007/s00726-016-2242-z
|View full text |Cite
|
Sign up to set email alerts
|

Epitope location for two monoclonal antibodies against human cystatin C, representing opposite aggregation inhibitory properties

Abstract: Human cystatin C (hCC), like many other amyloidogenic proteins, dimerizes and possibly makes aggregates by subdomain swapping. Inhibition of the process should suppress the fibrillogenesis leading to a specific amyloidosis (hereditary cystatin C amyloid angiopathy, HCCAA). It has been reported that exogenous agents like monoclonal antibodies against cystatin C are able to suppress formation of cystatin C dimers and presumably control the neurodegenerative disease. We have studied in detail two monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The choice of two monoclonal antibodies Cyst10 and Cyst28 may be of special importance as they possess opposite inhibitory properties toward the dimerization of human cystatin C. HDX-MS experiments confirmed our earlier results (Śladewska et al 2011), indicating that the epitopes for both antibodies are of discontinuous type and are located in the middle part as well as in the C-terminal part of the cystatin C molecule. It was found that the Cyst10 antibody recognizes two fragments which are located in two loops of the hCC structure (53–61—loop L1, 101–112—loop L2, see Figs.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The choice of two monoclonal antibodies Cyst10 and Cyst28 may be of special importance as they possess opposite inhibitory properties toward the dimerization of human cystatin C. HDX-MS experiments confirmed our earlier results (Śladewska et al 2011), indicating that the epitopes for both antibodies are of discontinuous type and are located in the middle part as well as in the C-terminal part of the cystatin C molecule. It was found that the Cyst10 antibody recognizes two fragments which are located in two loops of the hCC structure (53–61—loop L1, 101–112—loop L2, see Figs.…”
Section: Discussionsupporting
confidence: 89%
“…The hCC epitopes recognized by Cyst10 and Cyst28 previously defined by MS-coupled limited proteolysis are of the discontinuous kind. The present results from the HDX-MS approach are mostly in accordance with the epitopic sequences obtained by proteolytic excision/extraction (Śladewska et al 2011). In addition, we made an attempt to localize with the HDX-MS approach the epitopes for natural, polyclonal anti-hCC autoantibodies (NAbs) isolated from human IgG fraction, and compare them with our previous results obtained using an MS-assisted proteolysis approach (Johnstone and Thorpe 1996).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations